Epistemic Motivation and the Structure of Moral Intuition: Dispositional Need for Closure as a Predictor of Individualizing and Binding Morality. Issue 3 (18th April 2016) - Federico, Christopher M.; Ekstrom, Pierce; Tagar, Michal Reifen; Williams, Allison L.
Abstract: Moral foundations theory argues that morality encompasses both group‐preserving binding concerns about in‐group loyalty, authority and purity and individualizing concerns about harm avoidance and fairness. Although studies have examined the relationship between sociopolitical attitudes and the moral foundations, the relationship between individual differences in epistemic motivation—as indexed by need for cognitive closure—and moral intuition remains unexplored. Given the role of groups in providing epistemic security, we hypothesized that the need for closure would be most strongly related to support for the foundations most central to the regulation of group ties, that is, the binding foundations as opposed to the individualizing ones. Data from three samples provided evidence for this. Unpacking this pattern, we also found that those high in need for closure endorsed all foundations, whereas those low in need for closure emphasized only the individualizing ones. Finally, we found that the relationship between need for closure and the binding foundations was mediated by right‐wing authoritarianism, an orientation closely linked to a desire for the preservation of conventional in‐group morality. Copyright © 2016 European Association of Personality Psychology